2020
DOI: 10.21608/ejabf.2020.103630
|View full text |Cite
|
Sign up to set email alerts
|

Marine Algae in Egypt: distribution, phytochemical composition and biological uses as bioactive resources (a review)

Abstract: Algae are photosynthetic organisms with a wide variety of forms ranging from unicellular to multicellular macroalgae (Çakir Arica et al., 2017). Marine algae contain a number of different species, which are usually divided into two classes, microalgae and macroalgae in particular. Microalgae species like phytoplankton survive suspended in the water column, while macroalgae (commonly referred to as seaweed) are plant-like organisms that range in size from a few centimeters to several meters in length (Hernández… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…Also, Morsy et al (2014) reported Spirulina rich in calcium (1.044%) and iron (0.339%). Brown algae (Sargassum muticum) which were collected from the Egyptian Mediterranean Sea coast, contained high levels of sodium, calcium, and potassium, as well as moderate concentrations of iron ,and zinc ( Salem et al, 2018 andRashad &El-Chaghaby, 2020). On the other hand, it was lower than that reported by Sanchez et al (2003) who found that calcium and sodium values in spirulina were 120 and 2200 mg/100g respectively.…”
Section: Chemical Compositionmentioning
confidence: 78%
See 1 more Smart Citation
“…Also, Morsy et al (2014) reported Spirulina rich in calcium (1.044%) and iron (0.339%). Brown algae (Sargassum muticum) which were collected from the Egyptian Mediterranean Sea coast, contained high levels of sodium, calcium, and potassium, as well as moderate concentrations of iron ,and zinc ( Salem et al, 2018 andRashad &El-Chaghaby, 2020). On the other hand, it was lower than that reported by Sanchez et al (2003) who found that calcium and sodium values in spirulina were 120 and 2200 mg/100g respectively.…”
Section: Chemical Compositionmentioning
confidence: 78%
“…Different types of microalgae are considered a good source of natural alternative nutrients due to the capability of producing beneficial nutritive compounds which are useful for many purposes, such as ingredients for nutraceuticals or food additives, natural colorants, pharmaceuticals, and animal feed (Koyandea et al, 2019). Many microalgae species are rich in nutritionally useful constituents such as carbohydrates, proteins, basic amino acids, polyunsaturated fatty acids which are considered an adequate source of vitamins such as vitamins A and E as well as minerals such as potassium, iron, magnesium and calcium (Rashad and El-Chaghaby, 2020). Due to the high content of major bioactive compounds in the algae, they could possess therapeutic benefits as antiviral (Santoyo et al, 2012), anti-diabetic (Ali et al, 2017), antioxidant (Maeda et al, 2018), antiinflammatory (Lee et al, 2017), antibacterial (Capillo et al, 2018) and antitumoral (Lind et al, 2013 andLauritano et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Jania rubens that hosts diverse amphipod species (Kh. Gabr et al, 2020) are also known for its diverse haplotypes (Harvey et al, 2020) and bioactive resources (Rashad and El-Chaghaby, 2020). Further studies could explore, if DNA barcodes could effectively delineate various haplotypes of J.…”
Section: Dna Barcoding Rhodophyta and Its Utilitymentioning
confidence: 99%
“…Egypt which occupies a strategic geographical location straddling both the Mediterranean and the Red Sea, the two main enclosed coastal seas in the world, is considered one of the major producers of the marine flora in the Middle East 7 . In spite of enormous resources enriched with pharmacologically active chemical entities, the studies of seaweeds in Egypt are sparse and scattered.…”
Section: Introductionmentioning
confidence: 99%